“Why Do I Need to Sign it? Issues in Carrying Out Child Assent in School-Based Prevention Research Within a First Nation Community - Baydala, Lola; Letendre, Sherry; Ruttan, Lia; Worrell, Stephanie; Fletcher, Fay; Letendre, Liz; Schramm, Tanja (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2011)
The practice of and procedures for obtaining child assent in research involving children are based in Western conceptions of individual decision-making rights, free from any form of coercion including that of parents. In the context of obtaining assent for children involved in research in an Alberta First Nation, the issue can become more complex given respect for ethical frameworks based in collective decision-making and the responsibility of Elders and families to protect children in interactions with Western institutions. This article explores the results of a focus group held to discuss our experience with child assent in research taking place with a community-initiated and culturally-adapted substance abuse prevention program being taught in the community school. In this case the process of being asked to sign written individual assent in the classroom was perceived as bearing extrinsic risk. Given collective cultural norms, the communities past experiences with the safety of signatures, and the proper roles of Elders and family, the children asked “Why do I have to sign it” when asked to sign their assent for participation in the project. A process that involved gathering child assent with children surrounded by family and community was recommended. Greater researcher and REB responsiveness to the issue of non-malfeasance is needed, in this case, by not asking researchers and community members to act in ways that violate culturally-based ethical norms and protocol all of which are important to community continuity, self-determination, and well-being.